Veterinary Excipients in the Environment: Regulatory Blind Spots, Unanswered Questions, and Agricultural Sustainability — A Critical Review (Development Engineering Conferences Center Articles Database, 2026)
Veterinary excipients make up 60 to 90 percent of most drug formulations. Yet current environmental risk assessment frameworks focus almost exclusively on active pharmaceutical ingredients. Regulators legally consider excipients as "inert" substances. This review challenges that assumption.We examined 26 studies published between 2002 and 2026. The evidence shows that many excipients are not inert. Some surfactants like polyethoxylated tallow amine are thousands of times more toxic than active ingredients. A large-scale screening study identified 25 excipients with biological target activities, including thimerosal with dopamine receptor binding at 210 to 320 nM.Environmental fate data reveals serious problems. Synthetic polymers like polyvinylpyrrolidone and polyvinyl alcohol show negligible biodegradation. PVP exhibits only 1 to 4 percent degradation in soil. It simply dissolves and disperses into water compartments. These polymers accumulate in rivers at concentrations of 0.16 to 0.18 mg/L.Current monitoring systems do not measure excipients. The EU Rapid Alert System targets only pharmacologically active substances. Analytical methods are validated for active ingredients only. No maximum residue limits exist for excipients, despite the official definition of drug residues explicitly including them.Regulatory frameworks have other blind spots. Mixture effects between excipients and active ingredients are ignored. Legacy products authorized before environmental risk assessment guidelines were adopted have never been reviewed. Pharmacovigilance requirements for environmental effects remain undefined. Compliance with risk mitigation measures has no legal consequences.Some solutions exist. Biodegradable excipients from marine and renewable sources can reduce environmental persistence. Life cycle assessments show 40 to 60 percent emission reductions with green alternatives. But no veterinary-specific regulations require their use.This review concludes that veterinary excipients represent a critical regulatory blind spot. We recommend mandatory environmental risk assessment for excipients, including biodegradability testing. Monitoring programs should be established for excipients in manure, soil, and water. Until these changes occur, veterinary excipients will remain an unregulated threat to agricultural sustainability.